RIGHTS AND PROTECTION OF LIVING BEINGS IN ISLAM: AN ANALYTICAL STUDY - Ali Haidar; Rab Nawaz (Journal of Religion and Society, 2025)
Islam is a code of life and a religion of nature. Islam has emphasized the rights of animals living alongside humans, regardless of their likes or dislikes. In the light of the biography of the Prophet Muhammad (peace be upon him), it is found in history and hadiths that he was compassionate towards animals and advised his companions (may Allah be pleased with them) to respect the rights of animals and treat them with compassion. Where animals were mistreated, he forbade them and expressed his displeasure. There are many instances where he taught the rights of animals. Here are a few of them. In the light of these traditions, we are now being advised to treat animals well and fulfill their rights. Keywords: Islam, Protection, Animals, Rights